Thrombin Formation in Purified Systems - Surgenor, Douglas M; Steele, Barbara B; Wallach, Donald F. H (Thrombosis and Haemostasis, 1959)
Study of the kinetic behavior of purified human clotting factors suggests that formation of prothrombin activator from platelets, plasma thromboplastin component (PTC), antihemophilic factor (AHF), Factor V and calcium proceeds by a sequence of reactions. The earliest detectable reaction is slow and involves platelets, PTC and calcium; an intermediate activated PTC is obtained which is free of platelet contamination and is characterized by its kinetic behavior. Platelets are also requisite at a later step in the sequence, possibly in an intermediate formed between activated PTC, AHF, platelets and calcium. Variations in platelets, AHF and PTC result in characteristic responses in the kinetics of thrombin formation.